P2_8 Ciaphas Cain makes a splash - Carter, Samuel; Lyons, Hannah; Nixon, Joshua; O'Sullivan, Rachael (Physics Special Topics, 2022)
In the novel Ciaphas Cain: The Last Ditch by Sandy Mitchell [1], Ciaphas Cain crashes onto an ice world aboard a transport freighter. We calculate that the heat of the hull, as described in the book, would melt 4.5×1011kgof ice. While this is very large, the ship is too so we believe this value would be accurate